Comparisons of the Super-resolution TOA/TDOA Estimation Algorithms - Gao, Caicai (2018)
In order to separate signals from different sources while estimating time of arrival (TOA), the super-resolution technique in range/time domain is desirable in the scenario of multi-target with high density or in the presence of strong multipath, due to the limitation on the bandwidth. In this paper, we provide an overview of several existing range super-resolution algorithms, including the adaptive regularization least squares (APLS) method, the inverse filter (IF), the iterative adaptive approach (IAA), the multiple signal classification (MUSIC) algorithm using cross correlation (MUSIC-CC), and the MUSIC algorithm based on channel response (MUSIC-CR). Both numerical data and trial data transmitted and received by the universal software radio peripheral (USRP) are used to compare their performance.